Aplikasi Modern Wound Care pada Perawatan Luka Infeksi di RS Pemerintah Kota Padang : Application of Modern Wound Care in Infection Wound Care in Padang City Government Hospital - Rika Fatmadona; Elvi Oktarina (Fakultas Keperawatan Universitas Andalas, 2016)
Using modern wound care dressings began to flourish in Indonesia. The change can be seen from the previous majority of caregivers believe the best make up wound healing environment remains dry wound began to turn into wound care with moisture balance method. This activity aims to share knowledge with the nurses in Surgical department Dr. M. Djamil Hospital Padang on the basis of modern wound care and everyday applications. This activity lasted for one day in the form of seminars and workshops attended by 60 people a surgical nurse. Materials provided not only on the basis of modern wound care, but also about the hospital regulation and health insurance (BPJS) regulations governing the use of the dressing method. Discussion and demontsrasi method used, so that nurses can better understand about modern wound care applications. In the future, need to be arranged procedural clear and an agreement from the medical and hospital pharmacy to use this method in treating injured patients, so the quality of service can be better.